Accidents involving motorcyclists and cyclists in the municipality of São Paulo: characterization and trends()() - Rodrigues, Cintia Leci (Rev Bras Ortop, 2014)
OBJECTIVE: To describe the characteristics of motorcycle and bicycle accident victims, according to notifications of suspected and confirmed accidents that have occurred in the municipality of São Paulo. METHOD: This was a descriptive epidemiological study. It covered all accidents (12,924) that occurred involving motorcycles (11,366) and bicycles (1558) between January 2011 and October 2013. Data in the Health Department's information system for surveillance of violence and accidents (SIVVA) was surveyed. RESULTS: Motorcycle accidents accounted for 52.1% of the cases notified and bicycles, 7.1%. Males predominated in both types of accidents: 81.6% and 80.6%, respectively. In the motorcycle accidents, the predominant age group among the victims was from 20 to 24 years. Both types of accidents occurred during the daytime (7:00–18:00 h): 37.4% and 27.0% respectively. Among the motorcycle accidents, the driver had been using alcohol in 3% and it was not possible to identify whether this had occurred in 67%. CONCLUSIONS: Public policies prioritizing financial and human resources applied toward reducing these types of accidents need to be brought in.